Fulminant elderly adult-onset Still disease effectively treated with tocilizumab and methotrexate: A case report. Issue 28 (15th July 2022) - Horiuchi, Yugo; Hashimoto, Kenichi; Horikoshi, Hideyuki; Sano, Azusa; Kawamura, Yusuke; Fujita, Naoya; Kimata, Motohiro; Ono, Yosuke; Obuchi, Yasuhiro; Makino, Arisa; Kaneko, Mayuko; Kimura, Fumihiko; et al.
Abstract : Rationale: Adult-onset Still disease (AOSD) is a rare inflammatory disease of unknown etiology. AOSD is common in young or middle-aged adults; however, in recent years, there have been increasing reports of elderly AOSD. Differentiating AOSD from diseases such as infections and malignancies is difficult. Moreover, rare fulminant AOSD cases with resistance to corticosteroids and immunosuppressive drugs have been reported. Patient concerns: An 80-year-old woman presented with flaccid fever, generalized arthralgia, and erythema of the anterior chest for 2 weeks. On day 5 of hospitalization, the patient developed pleural effusion with hypoxemia and her vital signs indicated rapid progression to shock. During the clinical course, the levels of inflammatory markers, including maximum level of ferritin and white blood cells (WBCs) were elevated (252, 796 ng/mL and 86, 500/μV, respectively) with disseminated intravascular coagulation syndrome (DIC) and macrophage activation syndrome (MAS). Diagnosis: The patient was diagnosed with elderly AOSD as per the Yamaguchi criteria for AOSD. The state of disease was extremely severe with rapid progression and was, thus, categorized as a fulminant form of elderly AOSD. Interventions: The patient was treated with prednisolone (PSL) pulse therapy (1000 mg/d) twice and plasma exchange in the intensive care unit for the primary disease and shock. Although she recovered from shock, she developed DIC and MAS. Methotrexate (MTX; 10 mg/d) improved the DIC and MAS. However, severe pleuritis recurred and the patient developed pericarditis; her primary disease was poorly controlled. Finally, tocilizumab (TCZ) was introduced using interleukin-18 (IL-18) as a surrogate marker. The IL-18 level was measured repeatedly following admission, with the peak level (170, 000 pg/mL) recorded on the 75th day of hospitalization, immediately prior to introducing TCZ. Outcomes: The combined use of MTX, TCZ, and PSL was effective in suppressing elderly AOSD, which was unsuccessfully controlled with MTX and PSL. Frequent monitoring of IL-18 levels proved useful for differentiating elderly AOSD from other diseases. Lessons: A fulminant form of elderly AOSD was treated with a combination of MTX, TCZ, and PSL. Repeated monitoring of IL-18 levels can be useful for decision-making in treating elderly AOSD.